Magneto Optical Polarization Measurements using THz Polarization Modulation Spectroscopy - Stier, A. V.; George, D.; Markelz, A. G.; Cerne, J. (2011 36th International Conference on Infrared, Millimeter, and Terahertz Waves, 2011)
We report a new broad band technique for rapidly measuring the complex Faraday and Kerr rotations in materials such as topological insulators and graphene, combining the distinct advantages of THz time domain spectroscopy and polarization modulation techniques. The performance of the system is demonstrated using GaAs two dimensional electron gas in a magnetic field.
ISI Document Delivery No.: BJT73 Times Cited: 0 Cited Reference Count: 3 Cited References: Cerne J, 2000, PHYS REV B, V61, P8133, DOI 10.1103/PhysRevB.61.8133 Crassee I, 2011, NAT PHYS, V7, P48, DOI 10.1038/NPHYS1816 Tse WK, 2010, PHYS REV LETT, V105, DOI 10.1103/PhysRevLett.105.057401 Stier, A. V. George, D. Markelz, A. G. Cerne, J. Irmmw-thz Proceedings Paper 36th International Conference on Infrared, Millimeter, and Terahertz Waves (IRMMW-THz) Oct 02-07, 2011 Houston, TX Rice Univ, IEEE Microwave Theory & Tech Soc, NASA, California Inst Technol, Jet Prop Lab, Univ Wollongong George, Deepu/J-9882-2014 George, Deepu/0000-0003-0021-0705 345 e 47th st, new york, ny 10017 usa 2162-2027